(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The theme of the male-female dichotomy, the tensionbetween husband and wife, because of the incompatibility in their temperamentis present in many of Anita Desai’s novels. She is not interested inpre-marital relationship between man and woman but deals with the problems ofmarital relationship in all its dimensions and manifestations. Marriage whichis a means of self-fulfillment and self-knowledge eludes most women and failsto come up to their anticipation and aspirations.